Governança de terras no Alto Rio Pardo, semiárido mineiro: uma análise do Programa de Cadastro de Terras e Regularização Fundiária - Danilo Daniel Prado Araújo (2022)
The theme of land governance emerges on the international scene with the challenge of dealing with the multiple competing pressures around land use, seeking to balance economic growth and social justice. Brazil was one of the countries that understood its importance and took on the challenge of making it a reality. One of the ways adopted by the government to guide the theme was through partnerships with the states, which are responsible for the management of the developable lands. Among the partners is the agreement signed between the Union and the state of Minas Gerais, in 2015, which aims to implement the Land Registration and Land Regularization Program in the then Territory of The Upper Rio Pardo Citizenship (PCTRF-ARP). The Upper Pardo River concentrates the largest remaining developable public land of the State, arising from a discriminatory action of the 1980s, still inconclusive. This work is inserted in this context, whose objective was to analyze the PCTRF-ARP, in the municipality of Rio Pardo de Minas, in the light of land governance. To understand the land complexity of the territory and the municipality, a qualitative and quantitative research of exploratory character was adopted, starting from a historical approach with emphasis on the occupation and settlement of the territory; in the legal and institutional framework of the state of Minas Gerais; in public land programmes; traditional communities and recent occupation impulses of the municipality. Historically, the research reveals that several factors have contributed to the consolidation of the framework of weak land governance in the Upper Pardo River. Among them are state interventions. The PCTRF-ARP presents itself as an opportunity to begin the process of transition from a weak to a good governance of land. Despite the program's advances, there are still many challenges to achieve responsible land governance in the territory.